Hierarchical recruitment by AMPA but not staurosporine of pro-apoptotic mitochondrial signaling in cultured cortical neurons: Evidence for caspase-dependent/independent cross-talk - Beart, P.M. (2011)
10.1111/j.1471-4159.2007.04937.x